Comparative analysis of the philosophical heritage of B.F. Porshnev - Olga I. Rukavishnikova, Margarita P. Arutyunyan, Nikita V. Kishkin,; Lyudmila V. PyatiletovаElena G. Sakhnovskaya, (Opción, 2020)
The article is devoted to the study of nervous activity and its ability to generate any kind of subjective self-awareness via comparative qualitative research methods. As a result, a Soviet historian and an outstanding thinker who wondered about the beginning of human history created a model of consciousness that is very close to Metzinger’s theory of consciousness. In conclusion, the article is to honor the memory of Boris F. Porshnev and to support Thomas Metzinger’s theory of consciousness in order to provide an independent and emerging confirmation of his ideas in a completely different ideological environment